2002
DOI: 10.1097/00002030-200211080-00005
|View full text |Cite
|
Sign up to set email alerts
|

T-cell responses induced in normal volunteers immunized with a DNA-based vaccine containing HIV-1 env and rev

Abstract: We observed HIV-1 DNA plasmid vaccines induce CD4 T-helper cell responses in humans. We observed a discrepancy in the CD4 versus CD8 response suggesting the importance of analyzing both compartments in clinical evaluation. Furthermore, this report demonstrates the high level of immunogenicity of and its importance as a component of a prophylactic vaccine for HIV-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 30 publications
1
47
0
Order By: Relevance
“…In dose escalation studies, env and rev genes as well as regulatory genes appeared safe in HIV-1-infected individuals (71,72). It was possible to show the induction of substantial Ag-specific CD4 ϩ Th cells by DNA vaccination with regulatory genes rev, tat, and nef in patients and decreased viral loads with DNA representing the env and pol genes (73).…”
Section: Therapeutic Dna Vaccinesmentioning
confidence: 99%
“…In dose escalation studies, env and rev genes as well as regulatory genes appeared safe in HIV-1-infected individuals (71,72). It was possible to show the induction of substantial Ag-specific CD4 ϩ Th cells by DNA vaccination with regulatory genes rev, tat, and nef in patients and decreased viral loads with DNA representing the env and pol genes (73).…”
Section: Therapeutic Dna Vaccinesmentioning
confidence: 99%
“…DNA vaccination has emerged as an effective and safe strategy for inducing protective T cell immunity in preclinical models of infectious diseases (1). However, experiments in nonhuman primates and human trials suggested that DNA vaccines are not nearly as immunogenic in these species as they are in rodents (2)(3)(4)(5)(6). Several strategies to improve the immunogenicity of DNA vaccines have been described, but the level of improvement has been modest and not applicable to all Ags (7).…”
Section: Modulation Of the Immune Response Induced By Gene Electrotramentioning
confidence: 99%
“…Current gene-based immunogens, such as plasmid DNA and rAd5, have been widely studied in animal models [10][11][12][13][14][15], and have entered phase I and II human testing [16][17][18][19]. In addition, numerous groups have utilized vector prime, protein boost regimens to improve the potency or durability of the immune response to HIV or SIV antigens [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%